Kecemasan Keluarga Pasien Di Ruang Intensive Care Unit Rumah Sakit Umum Pusat Dokter Soeradji Tirtonegoro Klaten - Sugimin, Sugimin, Arum Pratiwi, S.Kp., M.Kes (2017)
Background: Critical condition of the patients admitted to the Intensive Care Unit enables the unexpected changes, the situation can lead to anxiety ranges is an adaptif response to the maladaptif response. This conditions affect for family function in daily life. The purpose of this study was to determine the anxiety based on adaptif and maladaptif physiological responses, and adaptif and maladaptif physiological responses of the family during waiting the family mambers in the Intensive Care Unit. The research method was descriptive analysis with the cross sectional approach, sampling technique used was quota sampling. The sample in this research was the nuclear family of patients who appropriate with the criteria that the nuclear family of patients, aged over 17 years old and in good health. The total sample of 30 respondents. Instruments in this study using the Zung Self-Rating Anxiety Scale. Descriptive analysis was utilized to analize the characteristics of respondents, adaptif maladaptif physiological responses and adaptif maladaptif psychological responses. The results of study showed thats respondents aged 17-25 years were 11 (36.7%), female gender 16 (53.3%), high school educated 17 (56.7%), working self-employed 12 (40.0%). Adaptif physiological responses were 11 (36.7%), maladaptif physiological responses were 19 (63.3%), psychological adaptif response of 16 (53.3%), maladaptif psychological response by 14 (46.7%). Conclusion: maladaptif physiological responses is greater than the adaptif response of the physiological and psychological adaptif response is similar to maladaptif psychological response.